PENERAPAN STRATEGI PEMBELAJARAN AKTIF BOWLING KAMPUS UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN DI KELAS XI SMA NEGERI 14 PEKANBARU - Romelda Felani; Jimmi Copriady; Roza Linda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research about application of bowling campus active learning strategy to improve student’s achievement on the topic of solvability and solvability product at class XI of SMA Negeri 14 Pekanbaru has been done. This research is experimental research based on pretest-posttest design. The sample consisted of two classes, XI IPA 2 as experiment class and XI IPA 3 as control class that randomly selected after testing normality and homogeneity. The bowling campus active learning strategy was applied in experiment class while in control class not applied. Analysis of data used t-test. Results of data analysis showed tcount>ttable (2,24>1,67), it means that the application of bowling campus active learning strategy can improve student’s achievement on the topic solvability and solvability product at class XI of SMA Negeri 14 Pekanbaru with an average N-gain experiment class 0,79 and N-gain control class 0,70 both of them included in the high category.Keywords: Bowling campus active learning strategy, Learning Achievement, solvability and solvability product.